Ground state of Bose gases interacting through singular potentials - Boßmann, Lea; Leopold, Nikolai; Petrat, Sören; Rademacher, Simone (Journal of Functional Analysis, 2026)
We consider a system of N bosons on the three-dimensional unit torus. The particles interact through repulsive pair interactions of the form N3β−1v(Nβx) for β∈(0,1)[jls-end-space/]. We prove the next order correction to Bogoliubov theory for the ground state and the ground state energy.
CRIS-Team Scopus Importer:2025-12-12
Keywords: Bogoliubov theory; Bose gas; Spectral estimates